G176 Untapping the hidden resource. (27th April 2016) - Hamilton, S; Filali, H; Fischer, M; McRobbie, C; Craddock, P
Abstract : Although adolescence represents a pivotal opportunity to enable young people with long-term conditions to fulfil their aspirations and to make better decisions about their health, this age group are rarely involved in healthcare redesign. Aims: To question the idea of users as passive consumers rather than active producers of care To renegotiate relationships between services users and professionals, which then empowers both parties To engage stakeholders across organisational boundaries to transform healthcare Methods: Our interdisciplinary team, drawn from the arts, technology and healthcare, takes a whole systems approach to improving health by working with young people, healthcare workers and commissioners. At time of increasing pressures on resources, we have taken the professionals out of the hospital to help them look not just at the symptom, but at the patterns that generate those symptoms. We have worked with adolescents (86% of whom are from Black Minority Ethnic groups), from concept, through to execution including presenting at conferences. We use technology as a lever to change the dynamic between patient and healthcare provider to improve outcomes, efficiency and engagement. To this end, we have co-produced films, mobile phone apps and workshops. Results: Better Conversations http://talklab.nhs.uk : A multimedia intervention to improve the complex consultation process between clinicians, young people, and carers. We created a coaching web-app for healthcare professionals, posters and patient leaflets. Pilot data on 20 clinicians shows an improvement in the composite score resulting from four questions around confidence in consultations from 63% to 80%. The Better Life Experiment : A programme of workshops supported by a smartphone app directed at improving transition as young people take on more responsibility for their care. Re-thinking Transition : A parallel workshop and multimedia web programme to train healthcare professionals in facilitating and supporting the Better Life Experiment and to deliver better patient-centred care. Conclusion: By involving patients in service design, we believe we have co-designed interventions with greater impact. We have used design thinking to create user-friendly solutions that enable adolescents to take ownership for their health. In a time of financial austerity we are using innovation to mobilise the resourcefulness of healthcare workers, patients, and families.